A Representation of Human and Nature in Saras Dewi’s Poem, Kekasih Teluk - Naufal Karim Siregar; Fitra Andira Wardana; Achmanuddin Berutu; Muhammar Ikbal; Purwarno Purwarno (International Journal of English and Applied Linguistics (IJEAL), 2024)
Literature possesses a unique ability to deeply engage human senses and emotions, forging a profound connection between individuals and the themes encapsulated within literary works. This research investigates the ecological themes interwoven throughout Saras Dewi's poem, Kekasih Teluk, offering a poignant reflection on humanity's relationship with the natural world. Employing a qualitative research approach rooted in the hermeneutic method, the research interprets Dewi's Kekasih Teluk to illuminate her exploration of environmental concerns such as deforestation, pollution, and biodiversity loss. Through careful analysis, the study reveals Dewi's critique of environmental exploitation, lamentation of ecological degradation, and advocacy for harmonious coexistence with nature. Drawing on ecocritical theory, which explores the intersections between literature and environmental consciousness, this research underscores the power of literature to inspire environmental awareness and action. Saras Dewi's Kekasih Teluk serves as a call for environmental stewardship and sustainable living, urging readers to reevaluate their relationship with the Earth. By elucidating the ecological narratives within Dewi's Kekasih Teluk, this analysis highlights the role of literature in fostering a deeper understanding of the intricate interplay between culture and the environment. Largely, this study emphasizes the transformative potential of literature in addressing pressing environmental issues and shaping attitudes towards ecological sustainability. Through critical analysis and interpretation, literature continues to serve as a catalyst for informed dialogue and proactive measures towards a more sustainable future.